Determinants of household indebtness: in the study of Australia / Nurnasuha Ziadee - Ziadee, Nurnasuha (Faculty of Business Management, University Teknologi MARA, 2018)
The continuous soaring upward of household indebtness in the Australia has become a worry to the general public and policy makers. It has increase substantially since 1980 and in recent years, the household debt to income ratio has hit almost 200 per cent which analyst have called it as extremely elevated as it also makes Australian household indebtness one of the highest in the world. International Monetary Fund (IMF) also warned Australia on its household indebtness vulnerability. However, what are the determinants that triggered these debts in Australia? Thus, this study is aimed to analyse the determinants that triggered the household indebtness in one of the developed countries, Australia. The continuous rising in household indebtness in Australia is derived from the factors of consumer price index (CPI), gross domestic product (GDP), housing price index (HPI), interest rate (INT), population (POP), and unemployment rate (U) in the Australia. This study is employing the multiple regression analysis. The expected finding is all the independent variables will have impact on the dependent variable. All the data is taken annually from year 1980 until 2016. Above all, this study could be beneficial to the whole economy and living standards in order for them to deal with better debt management as the surge in household indebt-ness can be a hazard to the economic system if the debt extents at an unsustainable level.